DISTRIBUTION OF Meloidogyne enterolobii IN GUAVA ORCHARDS IN THE STATE OF CEARÁ, BRAZIL - Silva, Maria do Carmo Lopes da (2017)
Among the factors negatively impacting guava (Psidium guajava) crop in Brazil, one of the most important is the root-knot nematode, Meloidogyne enterolobii, which may cause considerable yield losses and even the cessation of guava cultivation in some areas. In addition to affecting guava, the pathogen has been reported as a parasite in various other crops, among them both oleraceous and ornamental crops, as well as in spontaneous vegetation. The aim of this study was to verify the occurrence of M. enterolobii in plants collected in guava orchards in different counties of Ceará state, identified through electrophoresis with the isoenzyme esterase, and to observe its infecting behavior into Meloidogyne differentiating plants. Fifty root samples from guava, tasselflower (Emilia fosbergii), and jurubeba (Solanum paniculatum), were collected in 13 counties from eight micro-regions in the state of Ceará. In all analyzed samples, only esterase phenotype M2 (Rm: 0.6; 0.9), characteristic of M. enterolobii, was detected, showing that the nematode is widespread in orchards throughout the state, where is affecting these fruit tree, and that it is also able to parasitizing plants of the spontaneous vegetation. Based on the results, this nematode currently constitutes a serious threat to guava plantations in Ceará, and effective control mechanisms are crucial to prevent the spread of this pathogen to other, still unaffected, areas.